PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BSI KCP TULUNGAGUNG - Bhernanda Tri Mulia Aziza Putri Artino; Dede Nurohman (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
BSI is a merger of three Islamic bank namely Bank BRI Syariah (BRIS), Bank Syariah Mandiri (BSM) and BNI Syariah (BNIS). The existence of government policies to conduct mergers is expected to provide new financial institution options and prove that BSI has a strong track record in terms of performance. Performance is the result of work achieved by a person or group of people in an organization. This research aims to prove the new performance of BSI employees with this study entitled “Influence of Leadership, Motivation and Work Environment on Employee Performance of BSI KCP Tulungagung. The population in this study was employees of BSI KCP Tulungagung consisting of BSI KCP Tulungagung Sudirman and BSI KCP Tulungagung Trade Center. Quantitative desciptive analysis approach with saturated sampling analysis techniques and data acquistion of 56 respondents. The results of this study were leadership, motivation and work environment positively and significantly on employee performance on BSI KCP Tulungagung and a coefficient of determination (Adusted R Square) value of 0,784 which means 78,4% of leadership, motivation and work environment variables can explain employee performance variables and the remaining 21,6% are affected by other variables not described in the study.